Factores de riesgo para tuberculosis pulmonar pre extremadamente resistente en pacientes con tuberculosis pulmonar multidrogo resistente en el Hospital Regional Docente de Trujillo - Suarez Aguilar, Yajaira Marieli (2022)
Tuberculosis is the infectious disease responsible for the majority of deaths worldwide. The complex natural history of Mycobacterium tuberculosis means that people with latent and active infections must be identified. Also considering that resistant strains of tuberculosis are on the rise, as Multidrug Resistant (MDR) Tuberculosis is responsible for approximately a quarter of all deaths caused by antimicrobial resistant infections, and some of these strains extend resistance to Pre-extremely resistant tuberculosis (pre-XDR) it is necessary to identify the prevalence of the latter, in addition to the risk factors for this extension of resistance. Objectives: To determine the prevalence of pre-extremely resistant Tuberculosis in patients with multidrug resistant Tuberculosis. Also demonstrating if the consumption of psychoactive substances, HIV infection, 3-cross smear microscopy, malnutrition and a history of previous treatment for tuberculosis are risk factors for pre-extremely resistant pulmonary tuberculosis in patients with multidrug-resistant tuberculosis. Materials and methods: A case-control study of analytical, observational and retrospective design will be carried out, with data taken from the clinical history. The chi square statistical test will be used for qualitative variables; the associations will be considered significant if the possibility of being wrong is less than 5% (p < 0.05). In addition, the OR will be obtained for the risk factors regarding pre-XDR TB, if this is greater than 1, the 95% confidence interval will be calculated. And the multivariate analysis will be carried out through logistic regression for the intervening variables.